ABOUT IRRADIATION ABSORPTION ANOMALIES EFFECTS IN THE MEDIA WITH HELICAL PERIODICAL STRUCTURE - Gevorkian, A. A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2000)
This paper examines the transmission and reflection of light under normal incidence on a layer of a medium with a spiral periodic structure, the axis of which is perpendicular to the boundary surfaces. The influence of changes in various medium parameters (layer thickness, real and imaginary parts of the average permittivity, and dielectric anisotropy) on previously discovered effects is studied. The characteristics of anomalously strong absorption of radiation in periodic media near the diffraction reflection region are investigated. The physical mechanisms underlying the observed patterns are discussed.